Leadership as an Act of Love: Leading in Dangerous Times - Byrne-Jiménez, Mónica C.; Yoon, Irene H. (Frontiers in Education, 2019)
This essay is an invitation to engage in a heart-whole thought experiment around the possibilities and potential of framing leadership as an act of love. The current school context is defined by increasing pressures and demands that undermines the humanity of leaders, children and educators. In this context, leaders must find other ways to lead. The authors propose a framework offered to help leaders to reconnect with their love of children and education. They define the “habits of the heart” as harmony, courage, wisdom, and imagination. It is the combination of these habits that allow leadership with and through love. By defining these habits of heart, leaders can recognize them in their existing practice and find ways to enact new practices that create schools of learning and belonging.